The correlates of cognitive ageing and adoption of anti-ageing products among older adults - Ong, F.S.; Yap, Y.L. (2008)
Chronological age and cognitive age had a positive and significant relationship. The findings were consistent with past research suggesting that most people view themselves to be several years younger. As antecedents, biological changes and transitional life events showed a significant positive relationship with cognitive age. The relationship between cognitive and defensive ageing consumption activities was examined.